Thinking about informality: gender (in)equality (in) decent work across geographic and economic boundaries. (3rd April 2018) - Delaney, Annie; Macdonald, Fiona
ABSTRACT: Perspectives on the informal economy having evolved over time from a notion of a separate and disappearing sector to a broader focus that takes account of the wide range of economic activities that comprise informal work and focuses on processes and on the interdependencies of the formal and informal economic spheres. In this article we consider contemporary thinking about informal work and ask how useful the concept is for understanding changes occurring in work and employment in developed as well as developing economies so as to develop interventions to generate decent work. We use the lens of informality to explore how analysis of work and employment outcomes might give a more central place to the political and social location and, in particular, to gender in the construction of poor jobs. We propose that the concept of informality offered by feminist and other critical approaches is suitable for the analysis of much contemporary informalisation in both developed and developing economy contexts. We also propose that analysis can be strengthened through the adoption of the concept of 'invisibilisation'. We examine some particular types of feminised informal work in which there are high levels of vulnerability and disadvantage – homework and domestic and care work. We conclude that the constructs of informal work and informalisation of work can be used to highlight how gendered institutional and social processes construct work as beyond the effective reach of regulation.